2023
DOI: 10.12746/swrccc.v11i46.1141
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin - an antiviral drug for the COVID-19 pandemic?

Abstract: Abstract The use of ivermectin for the treatment of COVID-19 infections has been a subject of significant interest and controversy. The drug has a history of off-label use for a variety of clinical disorders and has shown some potential as an antiviral drug in in vitro studies and animal studies, and it has a relatively favorable safety profile. Multiple studies have been published examining the use of ivermectin against COVID-19. While several studies suggested it could be an effective therapeutic, most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
0
0
Order By: Relevance
“…Nevertheless, its optimal antiviral dose has not been determined, and the preliminary data do not illustrate a clear and comprehensive understanding of its effect in COVID-19. However, its effectiveness as an antivirus is still controversial, whilst latest studies have concluded that ivermectin has no benefit in the treatment of COVID-19 or needs very high and dangerous doses and for very long time [31,32].…”
Section: Othersmentioning
confidence: 99%
“…Nevertheless, its optimal antiviral dose has not been determined, and the preliminary data do not illustrate a clear and comprehensive understanding of its effect in COVID-19. However, its effectiveness as an antivirus is still controversial, whilst latest studies have concluded that ivermectin has no benefit in the treatment of COVID-19 or needs very high and dangerous doses and for very long time [31,32].…”
Section: Othersmentioning
confidence: 99%